Uji Kevalidan dan Kepraktisan Media Video Interaktif Berbasis Permainan Tradisional Sumatra pada Siswa Kelas 1 Sekolah Dasar - Jayanti, Salsabila Dwi; Istiq’faroh, Nurul; Pratama, Revid Dhimas (Innovations in Multidisciplinary Education Journal, 2026)
This study was motivated by the need for learning media that are interactive, contextual, and appropriate for the characteristics of early-grade elementary school students. In practice, classroom instruction is still often dominated by lecture methods, causing students to be less active, less interested in the material, and less likely to gain meaningful learning experiences, including in learning about local culture. This study aimed to develop an interactive video medium based on traditional games from Sumatra and to analyze its validity and practicality for first-grade elementary school students. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data were collected through expert validation questionnaires, teacher practicality questionnaires, and student response questionnaires. The results showed that the media achieved a validity percentage of 93%, which was categorized as very valid. The teacher practicality result reached 92%, categorized as very practical, while the student practicality result reached 94.71%, also categorized as very practical. The developed media integrates audio, visuals, text, animation, and simple letter and vocabulary recognition exercises through the context of traditional Sumatran games. Therefore, the interactive video based on traditional Sumatran games is feasible for use in learning because it supports engaging, concrete, and meaningful instruction while also introducing local culture to elementary school students.